2016
DOI: 10.1051/shsconf/20162601135
|View full text |Cite
|
Sign up to set email alerts
|

Delphi technique as a graduate course activity: Elementary science teachers’ TPACK competencies

Abstract: Abstract. This study aims to explore graduate science education students' views of elementary science teachers' TPACK competencies by employing a Delphi technique. 9 graduate science education students enrolled in a graduate course participated in the study. In the first round, participants were asked to list the competencies of an elementary science teacher with high level of TPACK and a total of 88 competencies were listed. In the second round, all participants investigated these competencies and eliminated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 8 publications
0
5
0
1
Order By: Relevance
“…Bao [22] suggests that teachers should be acquainted with their students' learning and cognitive levels, so that they can better match instructional activities to their students' online learning behavior. Angeli and Valanides [14] suggested that the teachers' practical ability to use technology is vital to their ability to integrate it into their teaching and create new learning opportunities; likewise, Aydin et al [23] pointed out that technology is only a tool to improve teaching practice. As Bai et al [24] asserted, when ICTs are integrated into instructional activities, the teacher is advised to provide guidance to students to effectively improve their learning outcomes.…”
Section: Educational Technology Used During the Covid-19 Pandemicmentioning
confidence: 99%
See 3 more Smart Citations
“…Bao [22] suggests that teachers should be acquainted with their students' learning and cognitive levels, so that they can better match instructional activities to their students' online learning behavior. Angeli and Valanides [14] suggested that the teachers' practical ability to use technology is vital to their ability to integrate it into their teaching and create new learning opportunities; likewise, Aydin et al [23] pointed out that technology is only a tool to improve teaching practice. As Bai et al [24] asserted, when ICTs are integrated into instructional activities, the teacher is advised to provide guidance to students to effectively improve their learning outcomes.…”
Section: Educational Technology Used During the Covid-19 Pandemicmentioning
confidence: 99%
“…Especially today, in an era of rapid technological change and proliferation, teachers should be sufficiently technologically literate to keep their students interested in learning and use technology to enhance learning outcomes [26]. However, the responsibility lies with them, not with the technology itself; as Aydin et al [23] pointed out, technology is only a tool and not the solution.…”
Section: Conclusion Limitations and Suggestions For Future Researchmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous academic research on teachers' knowledge of using technologies in teaching mainly adopted Mishra and Koehler's technological pedagogical content knowledge (TPACK) framework, whose limitations have been reported (i.e., Angeli and Valanides, 2009;Archambault and Barnett, 2010;Adam, 2016;Aydin et al, 2016;Baser et al, 2016;Peng and Daud, 2016), as well as other frameworks based on TPACK (i.e., Angeli and Valanides, 2009;Hsu and Chen, 2019). The present study adopted Hsu and Chen (2019) technology, learners, pedagogy, academic discipline content, and context knowledge (TLPACK) framework.…”
Section: Introductionmentioning
confidence: 97%